Development Of Defensive Training In Football Games For 12-Year-Olds - Pramono, Sigit Eko; Widodo, Achmad; Subagio, Irmantara; Wahyudi, Heri; Bulqini, Arif (Program Pascasarjana Universitas Negeri Jakarta, 2024)
The coaching program in Indonesia through the Indonesian football philosophy has not been detailed in the 12-year-old children's defensive training. This study aims to identify the importance of developing a defensive training model in football for 12-year-old children. This research uses a level 1 Research and Development (R&D) method. Design validation was carried out through FGD (Focus Group Discussion) involving three practitioner experts. The results of the study showed that there were problems related to physiology, child psychology and understanding of the concept of survival. This can be seen from the data that 88% of players selected by the national team coach for naturalization have characteristics as defensive players. Through the FGD, it was agreed and validated that the development of a defensive training model is very necessary, namely in the form of a guidebook and an animated video about defensive training movements in football for 12-year-old children. This is evidenced by data that 85% of both products are very feasible to be developed. This training model is expected to produce more defenders who have an understanding of tactics and a vision of playing football, so that both products can meet the needs of Indonesian national team defenders in the future